Anxiety, depression, and suicide risk among health workers during the COVID-19 pandemic - Regiane Lustosa da Cruz; Fernando José Guedes da Silva Júnior; Jaqueline Carvalho e Silva Sales; Maria Zélia de Araújo Madeira; Angélica Martins de Souza Gonçalves (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To evaluate the relationship between symptoms of anxiety, depression and risk of suicide in hospital health workers during the COVID-19 pandemic. Methods: This is a quantitative, cross-sectional, web survey-type study carried out with 270 health workers from a university hospital in September 2022, using an electronic form, in which the Hospital Anxiety and Depression Scale and questions of the Self-Reporting Questionnaire were used. Data were analyzed using SPSS Software, version 26. Described and inferential statistics were performed. The study was approved by the Research Ethics Committee, through Opinion number 5,625,667. Results: There was a prevalence of 40% for anxiety symptoms and 33% for depressive symptoms in female nursing professionals and that professionals who reported "ideas of ending life" increased the chances of presenting symptoms of anxiety and depression by 17,620 and 12,362 times, respectively. Conclusion: The findings of this study add to those already existing in the literature that highlights the need for investments in strategies to welcome and protect the health of healthcare personnel.